The psychosocial self-efficacy in adolescents with type 1 diabetes - Anne Survonen; Sanna Salanterä; Kirsi Näntö-Salonen; Arun K. Sigurdardottir; Riitta Suhonen (Wiley-Blackwell Publishing Ltd., 2022)
Aim: To analyse psychosocial self‐efficacy in adolescents with type 1 diabetes, evaluate associations between self‐efficacy and metabolic control and background variables and determine psychometric properties of the Finnish Diabetes Empowerment Scale (Fin‐DES‐28).
Design: A descriptive correlational survey.
Methods: The data were collected with the Finnish Diabetes Empowerment Scale from 13–16‐year‐old adolescents with type 1 diabetes (N = 189, 34%) in one university hospital district area in 2014.
Results: The level of psychosocial self‐efficacy was quite good. The highest scores were in managing the psychosocial aspects of diabetes, followed by assessing dissatisfaction and readiness to change and setting and achieving diabetes goals. The self‐efficacy did not correlate with metabolic control or background variables. A positive association was found between self‐efficacy and understanding of diabetes and its treatment, adjustment of diabetes to life and the relationship with the doctor and the nurse. The internal consistency of the Finnish Diabetes Empowerment Scale was adequate. The low response rate limits generalization.